Fast track surgery for anterior cruciate ligament reconstruction in military patients in Scotland. Issue 15 (10th November 2011) - Howes, J; Wood, A M; Bell, D J; Wrigley, S; Angus, C
Abstract : Military patients sustaining an Anterior Cruciate Ligament (ACL) injury are normally listed for "Fast-Track" surgery as the criterion for this is that they are likely to be fully fit for military employment within 12 months. All military patients in Scotland requiring ACL reconstruction should be referred through the Edinburgh Regional Rehabilitation Unit (ERRU) covering a population of 13 772 servicemen. All patients referred to ERRU over a 35 month period requiring ACL reconstruction were retrospectively followed for a minimum of 6 months post referral, with injuries and subsequent employment fitness recorded. 35 patients required "Fast Track" ACL reconstruction giving an incidence of 8.47/10 000/year. 30 patients (86%) had associated ipsilateral knee pathology: 15 (43%) had an associated medial meniscal injury, 16 (46%) lateral meniscal injury, and 16 (46%) had an osteochondral defects (OCD). Only 28/35 (80%) had their fitness outcome recorded. Of these patients 9 (32%) were fully fit, 8 (29%) had limitations, 11 (39%) Unfit. Patients with a combination of ACL, osteochondral defect and meniscal injury had the worst outcomes: Fully fit 2 (20%), limitations 1 (10%) and 7 (70%) unfit. (P=0.01) The mean time for return to full fitness was 13 months (range 8–17) 95% CI 2.17. ACL injury has significant morbidity with regards future military employment. In our study group, only 32% were regarded as fully fit and 39% were unfit. Patients with an associated meniscal and osteochondral defect have a poor prognosis. Further prospective research is required to ascertain which personnel should be referred for "Fast Track" surgery and which patients are unlikely to regain full military fitness so that patients can be fully consented about the full benefits of surgery preoperatively.